Risk Assessment Framework for Bridge Integrity Management System in Malaysia (BIMs) - WAN SALIM, WAN SAFIZAH (2021)
There is a huge number of highway bridges in most of the countries all around the world and the number keeps increasing yearly. Due to the large number of bridges to be monitored, it will contribute to the issue on the inspection and maintenance cost which must be given priorities during the decision-making process of which action should be taken. Furthermore, in most current practiced bridge management system still applying the defect based method through visual assessment at the inspection level with time-based inspection interval such between one-to-two-years gap. Thus, enhancement of current system in managing the bridge performance assessment is essential. Therefore, this study proposed the framework for risk-based inspection of management system for reinforced concrete highway bridge, namely Bridge Integrity Management Systems (BIMs) using risk based approach.